2011
DOI: 10.1177/0960327111421943
|View full text |Cite
|
Sign up to set email alerts
|

Piperine as an adjuvant increases the efficacy of curcumin in mitigating benzo(a)pyrene toxicity

Abstract: In the present study, the antioxidative and anticlastogenic effects of curcumin and piperine separately and in combination have been investigated against benzo(a)pyrene (BaP)-mediated toxicity in mice. Male Swiss albino mice were pretreated with curcumin (100 mg kg(-1) body weight) and piperine (20 mg kg(-1) body weight) separately as well as in combination orally in corn oil for 7 days; and subsequently, after 2 h of pretreatment, BaP was administered orally in corn oil (125 mg kg(-1) body weight). A single d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…This was in agreement with Biswas SK et al, [45], who stated that curcumin can induce glutathione synthesis and increase the level of GSH and glutamylcysteine ligase catalytic subunit mRNA expression in oxidant and TNF α treated cells. The results in this study indicates that, curcumin may have profound effects on cellular redox control and similar to the studies of Eybl V et al, [36] and Sehgal A et al, [46].…”
Section: Discussionsupporting
confidence: 92%
“…This was in agreement with Biswas SK et al, [45], who stated that curcumin can induce glutathione synthesis and increase the level of GSH and glutamylcysteine ligase catalytic subunit mRNA expression in oxidant and TNF α treated cells. The results in this study indicates that, curcumin may have profound effects on cellular redox control and similar to the studies of Eybl V et al, [36] and Sehgal A et al, [46].…”
Section: Discussionsupporting
confidence: 92%
“…The produced metabolites may damage DNA by forming adducts, but also through the induction of ROS that, besides DNA, may also damage proteins and lipids. These molecular alterations can be the subjacent origin of the presently observed increase in the number of SCE and CA, result which is in line with the genotoxic potential of BaP previously demonstrated in in vitro and in vivo short-term tests (Alvarez-González et al, 2011;Bhagavathy and Sumathi, 2012;Sehgal et al, 2012). In the case of BC, our results showed no capacity of the chemical to induce SCE and CA in mouse, a finding which is concordant with previous studies using bacterial tests, and the analysis of micronuclei in vitro and in vivo (Di Sotto et al, 2008Molina-Jasso et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…Respect to the first mentioned mechanism, it is pertinent to stress that a single administration of the mutagen resulted in a significant increase of lipoperoxidation and protein oxidation, suggesting an initial induction of oxidative stress in hepatic tissue that could be disseminated to all cells of the organism. In fact, BaP has been previously reported to increase lipoperoxidative products either by producing ROS or by decreasing the activities of antioxidant enzymes, as well as to increase the level of oxidized proteins in the liver of mice (Emre et al, 2007;Sehgal et al, 2012). These effects may lead to serious cellular damage including modification of cell structure, enzymatic activity, signaling pathways, and DNA damage Kryston et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed its anticancer potential against different types of hepatic, gastrointestinal, skin, lung, hematologic malignancies and many other types of cancers (Sehgal et al, 2012;Abouzied et al, 2015). Curcumin has been reported to exhibit its anticancer activity primarily through inhibition of carcinogen activation, stimulation of carcinogen detoxification, suppression of pro-inflammatory signaling, induction of cancer cell apoptosis, cell cycle arrest, inhibition of angiogenesis and metastasis, modulation of oncogenes and tumor suppressor genes (Rajasekaran, 2011).…”
Section: Introductionmentioning
confidence: 99%